2022
DOI: 10.1111/ejn.15676
|View full text |Cite
|
Sign up to set email alerts
|

Current perspectives on mitochondrial dysfunction in migraine

Abstract: Mitochondria are an autonomous organelle that plays a crucial role in the metabolic aspects of a cell. Cortical spreading depression (CSD) and fluctuations in the cerebral blood flow have for long been mechanisms underlying migraine. It is a neurovascular disorder with a unilateral manifestation of disturbing, throbbing and pulsating head pain. Migraine affects 2.6% and 21.7% of the general population and is the major cause of partial disability in the age group 15–49. Higher mutation rates, imbalance in conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 151 publications
(163 reference statements)
0
10
0
Order By: Relevance
“…In this study, we also found that proteins related to mitochondrial organization changed after PFO closure, meanwhile the brain of PFO‐positive mice also showed enrichment of electron transfer and GTPase activity. These energy metabolic processes are probably associated with pathogenesis of migraine and epilepsy 74,75 . In subgroup analysis of epilepsy and migraine, we found proteins related to pyruvate metabolism increased after PFO closure in the peripheral blood of PWEs.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In this study, we also found that proteins related to mitochondrial organization changed after PFO closure, meanwhile the brain of PFO‐positive mice also showed enrichment of electron transfer and GTPase activity. These energy metabolic processes are probably associated with pathogenesis of migraine and epilepsy 74,75 . In subgroup analysis of epilepsy and migraine, we found proteins related to pyruvate metabolism increased after PFO closure in the peripheral blood of PWEs.…”
Section: Discussionmentioning
confidence: 74%
“…These energy metabolic processes are probably associated with pathogenesis of migraine and epilepsy. 74,75 In subgroup analysis of epilepsy and migraine, we found proteins related to pyruvate metabolism increased after PFO closure in the peripheral blood of PWEs. Previous studies have found that pyruvate metabolism disorder related to epilepsy not only provides energy for the brain, but also plays a brain protective role.…”
Section: Discussionmentioning
confidence: 92%
“…There are similarities between the clinical features of migraine and MELAS (mitochondrial encephalomyopathy, lactic acidosis, and stroke‐like episodes) syndrome, which is primarily caused by a gene defect in mitochondrial DNA (mtDNA). A high prevalence of migraine was reported in individuals with certain mtDNA mutations 10,26 . Preclinical studies also demonstrated the activation of transient receptor potential ankyrin‐1 (TRPA1) in meningeal trigeminal nociceptors by reactive oxygen and nitrogen species (ROS/NOS), leading to neurogenic vasodilatation and CGRP release 21,27,28 …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, lactate levels were found to be high in migraine patients, indicating an impairment of mitochondrial metabolism in migraine 7,8 . Mitochondria regulates Ca 2+ homeostasis in excitable cells; however, mitochondrial dysfunction leads to abnormal Ca 2+ levels and excessive reactive oxygen species (ROS) production that may increase the possibility of migraine by inducing cortical spreading depression, a phenomenon underlying the migraine aura 9–11 . Moreover, disruptions in mitochondrial oxidative phosphorylation/brain oxidative energy metabolism during attack and attack‐free periods were displayed by phosphorus magnetic resonance spectroscopy studies 8,12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation